Establishing the need for a low‐cost Canadian debt relief procedure. (2nd January 2020) - Schwartz, Saul; Ben‐Ishai, Stephanie
Abstract: Canada does not have a low‐cost bankruptcy option for debtors with low incomes and low assets. In this article, we present empirical evidence of the need for such an option by estimating the number of debtors who might benefit from it. We then review the successful low‐cost bankruptcy options in operation in New Zealand and in the United Kingdom and recommend that Canada adopt a similar system.